Challenges and Strategies for Digital Literacy Ecosystem Development in the RI-RDTL Border Region - Jhon Enstein; Yonly Adrianus Benufinit; Femberianus Sunario Tanggur (STKIP Taman Siswa Bima, 2024)
This study aims to explore the challenges in building a digital literacy ecosystem in the Indonesia-East Timor border area, particularly in East Amfoang Sub-district. Using a descriptive qualitative approach. The results show that the majority of teachers face difficulties in accessing the internet and digital technology for learning activities, with 121 teachers reporting consistent difficulties. The challenges faced by the community are limited digital infrastructure, low economic capability and lack of digital literacy training, which hinder the utilization of technology in daily life and education. The findings highlight the importance of developing satellite-based or 5G internet infrastructure that can reach remote areas, as well as digital literacy training that focuses on practical skills for teachers and students. In addition, public education programs related to information safety and news source verification are also needed to increase public awareness of digital risks. Based on the research results, it is recommended to implement more equitable digital infrastructure development policies, community-based digital skills training, and collaboration between the government, educational institutions, and the private sector to create technology solutions that suit local needs. With these strategies, it is expected to reduce the digital divide and improve the quality of life and economic welfare of people in border areas.